Torture and ill-treatment in democratic Spain - Silvina Ribotta (Cuadernos Electrónicos de Filosofía del Derecho, 2020)
Torture in contemporary and democratic Spain is a worrying reality, as shown by reports from the most relevant international organizations in the fight against and prevention of torture, such as the European Committee for the Prevention of Torture of the Council of Europe, NGO’s, internal Spanish judgments and, grievously, judgments of the European Court of Human Rights. These sentences of the ECHR have found violations of article 3 of the European Convention on Human Rights, for not carrying out exhaustively and adequately the investigations into complaints of ill-treatment and torture, and in one case for inhuman treatment. These serious facts demand urgent democratic responses with direct and immediate political, legal, and social actions that imply the forceful rejection of them and the condemn of those responsible.